Leveraging IoT for Organizational Culture Transformation and Quality Improvement: A Case Study of PT Kabelindo Murni Tbk's Building Wire Production Line - Baharsyah, Ilham Baihaqi; Iqbal, Widy Maulana; Andika, Dade; Tyas, Ari Anggarani Winadi Prasetyoning (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The adoption of Internet of Things (IoT) technology at PT. Kabelindo Murni Tbk. marks a significant milestone in leveraging integrated systems. By using a single application, positioning the company as a pioneer in IoT implementation within Indonesia's cable manufacturing industry. Thus, in this study aimed to examines the impact of IoT adoption on technological adaptation between organizational culture change and corporate goals achievement. Here, the qualitative method is performed to analyze the organizational culture change from several respondent. In this study, the data taken from subjective experiences of respondent from 2 managers, 2 supervisors, 1 management trainee, and 5 production staff.  The parameter is includes improving product quality, optimizing energy resource usage, increasing the effectiveness of raw material utilization in cable production, and fostering changes in organizational work culture using IoT technology at PT. Kabelindo Murni Tbk. The result shows an adaptation IoT as a new technology is increasing decision-making processes, productivity, efficiency, effectiveness, and product quality. Thus, the IoT technology can improve organizational work in the company especially over wire production line.